The cat screams - Downing, Todd; Hoffman, H. Lawrence; Popular Library (New York, N.Y.) (Popular Library, 1945)
At a quarantined Mexican pension, the resident cat screams whenever death is about to strike one of the guests. Hugh Rennert, a customs agent and amateur detective, must unmask a murderer and end the deadly rampage.
Reprint. Originally published: Garden City, N. Y. : Doubleday, Doran & Co., 1934
"A Hugh Rennert mystery"--T.p.
Reginald, R. Cumulative paperback index, 1939-1959,page 57
Schreuders, P. Paperbacks, U.S.A.,page 191
At a quarantined Mexican pension, the resident cat screams whenever death is about to strike one of the guests. Hugh Rennert, a customs agent and amateur detective, must unmask a murderer and end the deadly rampage.
Keywords: Resorts / Mexico / Fiction.; Murder / Investigation / Fiction; Taxco de Alarcón (Mexico) / Fiction.; Pulp fiction. / aat; Pulp literature, American.; Detective and mystery fiction / lcgft